Pedagogy training among political scientists: Opportunities, interest, and obstacles. (22nd December 2021) - Trowbridge, David; Woodward, Jennifer
Abstract: Over the last two decades there have been periodic calls for improved teacher training and a growth in scholarship on teaching and learning. Yet, we know little about opportunities and participation in training programs. What kinds of training are political scientists collectively engaging in, especially for tenured and tenure track faculty? Are political science departments providing training programs for both faculty and graduate students? With the cooperation of the American Political Science Association, we included five questions about pedagogical training in a survey of Teaching and Learning Conference participants and in a survey of APSA members in 2018. We find that there is interest in different kinds of training experiences, but most of the training takes place outside the department. Within departments, there may be resource and culture-related obstacles to offerings and participation. Results indicate a need for more resources and career-related incentives in order to encourage participation in these opportunities.